2005
DOI: 10.1159/000086292
|View full text |Cite
|
Sign up to set email alerts
|

Myelination of the Pig’s Brain: A Correlated MRI and Histological Study

Abstract: Minipigs, 2, 4, 6 months old, were used to evaluate the relationship between myelination in the fiber tracts of the central nervous system (CNS) of this animal during development. Histological results showed an increased density of the myelinated fibers as well as branching of these fibers in the areas studied, including the cortical white matter, olfactory tract, the corticospinal tract, the fasciculus cuneatus and the spinal V nucleus from 2 to 6 months old. By 6 months, the pig was sexually matured. Concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…They demonstrated the usefulness of fMRI in non-anaesthetized piglets to identify differences in brain activation induced by pain stimulation and passive movement (Fang et al 2005b). Immunohistochemistry enabled the authors to propose a hypothesis of functional brain maturation to explain the effect of age on brain activation measured by fMRI (Fang et al 2005a). It has also been demonstrated that the volumetric analysis of brain lesions by MRI reveals the impact of traumatic brain injury in a similar way to histological approaches (Grate et al 2003; Fig.…”
Section: Brain Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…They demonstrated the usefulness of fMRI in non-anaesthetized piglets to identify differences in brain activation induced by pain stimulation and passive movement (Fang et al 2005b). Immunohistochemistry enabled the authors to propose a hypothesis of functional brain maturation to explain the effect of age on brain activation measured by fMRI (Fang et al 2005a). It has also been demonstrated that the volumetric analysis of brain lesions by MRI reveals the impact of traumatic brain injury in a similar way to histological approaches (Grate et al 2003; Fig.…”
Section: Brain Injurymentioning
confidence: 98%
“…For example, Fang and collaborators studied the development of the pig brain (Fang et al 2005a) and compared nociceptive and motor stimulations at different ages (Fang et al 2005b). They demonstrated the usefulness of fMRI in non-anaesthetized piglets to identify differences in brain activation induced by pain stimulation and passive movement (Fang et al 2005b).…”
Section: Brain Injurymentioning
confidence: 99%
“…the brain of guinea pig, sheep and monkey, which has a prenatal growth spurt, or the brain of rat and rabbit, which develops postnatally (Dobbing and Sands, 1979). The development of the pig brain is also considered more similar to the human brain with respect to myelination, compositions and electrical activity (Dickerson and Dobbing, 1966;Fang et al, 2005;Flynn, 1984;Pampliglione, 1971;Thibault and Margulies, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…On account of that, understanding the sectional anatomy of the normal brain and related structures and MR imaging features of the tissues are quite important in the diagnosis and treatment of clinical diseases, experimental studies and also imaging anatomy of the head (4). In our literature review, it was noticed that the anatomical based MRI studies about the pig brain wasn't satisfactory (8,17,25). The purpose of the study was to define imaging features of the normal structures of the head and to provide an overview of MR imaging anatomy of the brain and surrounding structures in the pig.…”
Section: Introductionmentioning
confidence: 99%